1983
DOI: 10.1029/ja088ia05p04041
|View full text |Cite
|
Sign up to set email alerts
|

Mirror instability and the origin of morningside auroral structure

Abstract: The Laboratory Operations of The Aerospace Corporation is conducting experimental an(l theoretical investigations necessary for the evaluation and application of seientific advances to new military space systems.Versatility and flexibility have been developed to a high degree by the laboratory personnel in dealing with the many problems encountered in the nation's rapidly developing space sysu~ms. Expertise in the latest: scientific developments is vita] to the accomplishment of tasks related to these problems… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
14
0

Year Published

1985
1985
2015
2015

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 47 publications
1
14
0
Order By: Relevance
“…They also remarked that the general eastward drift of the observed black patches is consistent with the gradient-B curvature drift of trapped energetic electrons in the magnetosphere, and suggested that the black patches might represent structures in the high-energy electron population, without specifying what these "structures" could be. This model is based on the work by Chiu et al (1983), who argued that the precipitating hot electrons that create optical signatures are gradient drifting azimuthally on trajectories which can depart significantly from the ionospheric convection path. Results from combined FAST and airborne auroral imager studies by Peticolas et al (2002) indicate (their Fig.…”
Section: Discussion and Resultsmentioning
confidence: 99%
“…They also remarked that the general eastward drift of the observed black patches is consistent with the gradient-B curvature drift of trapped energetic electrons in the magnetosphere, and suggested that the black patches might represent structures in the high-energy electron population, without specifying what these "structures" could be. This model is based on the work by Chiu et al (1983), who argued that the precipitating hot electrons that create optical signatures are gradient drifting azimuthally on trajectories which can depart significantly from the ionospheric convection path. Results from combined FAST and airborne auroral imager studies by Peticolas et al (2002) indicate (their Fig.…”
Section: Discussion and Resultsmentioning
confidence: 99%
“…The idea is not theoretically new. Chiu et al [1983] proposed that the spatial modulation of the equatorial magnetic field and ambient plasma by a mirrormode wave, which is also the suggested mechanism of our observed ULF waves [see also Takahashi et al, 1990], can modulate the growth rate of the electron cyclotron waves, either electromagnetic or electrostatic, and in turn modulate the precipitation rate of auroral electrons. Also, AshourAbdalla and Kennel [1978] found that the local growth rate and spatial amplification of the ECH instability are crucially controlled by the "cold" electron plasma and/or its ratios to the "hot" population in density and temperature.…”
Section: Discussionmentioning
confidence: 99%
“…46). Chiu et al (1983) have argued that the velocity shear associated with the underlying magnetospheric convec tion pattern should tend to align any spatial maxima in auroral-electron precipitation with equipotentials of the convection eletric field. 38.…”
Section: It Has Been Noted In Connection Withmentioning
confidence: 99%
“…Ion velocity distributions(Chiu et al, 1983), represented via contours of constant and equally spaced logio/, that would theoretically result from mappings (consistent with Liouville*s theorem) from source locations to (L, Φ) = (7, ± 7Γ/2). Sources: (a) a Maxwellian of temperature 1 keV at L = 13; and (b) a field-aligned beam of directed energy 0.5 keV and temperature 0.5 keV at L = 10 (sin φ < 0).…”
mentioning
confidence: 91%